Innovation and development of China Machine Press in the new century - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
On September 15, 2012, China Machine Press (CMP) held its 60th anniversary ceremony in Jingxi Hotel in Beijing. The president of CMP, Mr Wang Wenbin, delivered a warm speech: 'After 60 years of development, China Machine Press has become one of the largest technical information service institutions in the field of Chinese industries, and become the publisher owning the largest share of China's book retail market. In 2012, CMP's annual book sales reached 35 million copies, issued periodicals hit 7 million copies, sales revenues exceeded 950 million Yuan, and tangible assets topped 1.3 billion Yuan. CMP has become a service entity of information collection, value-added information processing, and communication services'. This case study discusses this topic.